Load-Dependent Changes in Left Ventricular Structure and Function in a Pathophysiologically Relevant Murine Model of Reversible Heart Failure. (May 2018) - Weinheimer, Carla J.; Kovacs, Attila; Evans, Sarah; Matkovich, Scot J.; Barger, Philip M.; Mann, Douglas L.
Abstract : Background: To better understand reverse left ventricular (LV) remodeling, we developed a murine model wherein mice develop LV remodeling after transverse aortic constriction (TAC) and a small apical myocardial infarct (MI) and undergo reverse LV remodeling after removal of the aortic band. Methods and Results: Mice studied were subjected to sham (n=6) surgery or TAC+MI (n=12). Two weeks post-TAC+MI, 1 group underwent debanding (referred to as heart failure debanding [HF-DB] mice; n=6), whereas the aortic band remained in a second group (heart failure [HF] group; n=6). LV remodeling was evaluated by 2D echocardiography at 1 day, 2 weeks and 6 weeks post-TAC+MI. The hearts were analyzed by transcriptional profiling at 4 and 6 weeks and histologically at 6 weeks. Debanding normalized LV volumes, LV mass, and cardiac myocyte hypertrophy at 6 weeks in HF-DB mice, with no difference in myofibrillar collagen in the HF and HF-DB mice. LV ejection fraction and radial strain improved after debanding; however, both remained decreased in the HF-DB mice relative to sham and were not different from HF mice at 6 weeks. Hemodynamic unloading in the HF-DB mice was accompanied by a 35% normalization of the HF genes at 2 weeks and 80% of the HF genes at 4 weeks. Conclusions: Hemodynamic unloading of a pathophysiologically relevant mouse model of HF results in normalization of LV structure, incomplete recovery of LV function, and incomplete reversal of the HF transcriptional program. The HF-DB mouse model may provide novel insights into mechanisms of reverse LV remodeling. Abstract : Supplemental Digital Content is available in the text.